Implementation of Marketing Strategy At J&C Cookies Bandung in an Effort to Increase Sales: Implementasi Strategi Pemasaran Pada J&C Cookies Bandung dalam Upaya Meningkatkan Penjualan - Mochamad Rizal Yulianto; Gustiawan Budi Pradana; Mahda Mufarrikhah; Chofivah Alif Tiani; Ariska Putri Ramadhani (Procedia of Social Sciences and Humanities, 2026)
This article aims to examine the implementation of marketing strategies implemented by J&C Cookies Bandung in an effort to increase sales volume. The Food and Beverage (F&B) sector in Indonesia, especially the cake and snack category, shows significant growth along with increasing public demand. As one of the key players in this sector, J&C Cookies must implement appropriate and flexible marketing strategies. This study uses a qualitative descriptive method with a field research approach. Data collection was carried out through observation, in-depth interviews, and document collection. The research findings show that J&C Cookies implements various marketing strategies, including digital marketing, branding, product development, pricing, distribution, and promotion. The effective implementation of the marketing mix (7P) and the STP (Segmentation, Targeting, Positioning) approach has been proven to increase sales and expand J&C Cookies' market share. Highlights: Integrating the 7P principles with targeting approaches broadens consumer reach significantly. Deploying physical storefronts alongside digital reseller networks optimizes product accessibility. Seasonal influencer collaborations combined with aesthetic packaging successfully secure competitive advantages. Keywords: Digital Promotion, Distribution Networks, Aesthetic Packaging, Target Segmentation, Influencer Collaborations